Cinematic encounters 2 : portraits and polemics - Rosenbaum, Jonathan, 1943- (University of Illinois Press, 2019)
Eschewing the idea of film reviewer-as-solitary-expert, Jonathan Rosenbaum continues to advance his belief that a critic's ideal role is to mediate and facilitate our public discussion of cinema. Portraits and Polemics presents debate as an important form of cinematic encounter whether one argues with filmmakers themselves, on behalf of their work, or with one's self. Rosenbaum takes on filmmakers like Chantal Akerman, Richard Linklater, Manoel De Oliveira, Mark Rappaport, Elaine May, and Bela Tarr. He also engages, implicitly and explicitly, with other writers, arguing with Pauline Kael--and Wikipedia--over Jacques Demy, with the Hollywood Reporter and Variety reviewers of Jarmusch's The Limits of Control, with David Thomson about James L. Brooks, and with many American and English film critics about misrepresented figures from Jerry Lewis to Yasujiro Ozu to Orson Welles. Throughout, Rosenbaum mines insights, pursues pet notions, and invites readers to join the fray.
Includes index.
Keywords: Motion pictures.; Motion picture producers and directors -- Interviews.; Motion picture actors and actresses -- Interviews.; Producteurs et réalisateurs de cinéma -- Entretiens.; Cinéma.; PERFORMING ARTS -- Reference.; PERFORMING ARTS -- General.; Motion picture actors and actresses; Motion picture producers and directors; Motion pictures; Interviews